Impact of Olive Saplings and Organic Amendments on Soil Microbial Communities and Effects of Mineral Fertilization - Llimós, Miquel; Segarra, Guillem; Sancho-Adamson, Marc; Trillas, M. Isabel; Romanyà, Joan (Frontiers in Microbiology, 2021)
Plant communities and fertilization may have impact on soil microbiome. Most commercial olive trees are minerally fertilized while this practice is being replaced by the use of organic amendments. Organic amendments can both fertilize and promote plant growth promoting organisms. Our aims were (i) to describe the changes in soil bacterial and fungal communities induced by the presence of young olive trees and their interaction with organic amendments and ii) to compare the effects of mineral and organic fertilization. We set up two parallel experiments in pots using a previously homogenized soil collected from a commercial olive orchard: in the first one we grew olive saplings in unamended and organically amended soils with two distinct composts and compared these two soils incubated without a plant while in the second experiment we comparatively tested the effects of organic and mineral fertilization. OTU’s and relative abundances of bacterial and fungal genera and phyla were analyzed by 16S rRNA and ITS1 gene amplicon using high-throughput sequencing. Basal respiration and substrate-induced respiration were measured by Microresp™. The effects of the different treatments were analyzed in all phyla and in the 100 most abundant genera. The presence of olive saplings increased substrate-induced respiration and bacterial and fungal richness and diversity. Organic amendments greatly affected both bacterial and fungal phyla and increased bacterial richness while not affecting fungal richness. Mineral fertilization increased the relative abundance of the less metabolically active bacterial phyla (Actinobacteria and Firmicutes) while it reduced the most metabolically active phylum, Bacteroidetes. Mineral fertilization increased the relative abundance of three nitrogen-fixing Actinobacteria genera while organic fertilization only increased one genus of Proteobacteria. In organically and minerally fertilized soils high basal respiration rates were associated with low fungal diversity. Basidiomycota and Chytridiomycota relative abundances positively correlated with basal respiration and substrate induced respiration, while Ascomycota correlated negatively. Indeed, Ascomycota phyla comprised most of the fungal genera decreased by organic amendments. The symbiotrophic phylum, Glomeromycota did not correlate with any of the C sources. The relative abundance of this phylum and genera was promoted by the presence of plants but decreased when amending soils with composts.